Blending of PLGA-PEG-PLGA for Improving the Erosion and Drug Release Profile of PCL Microspheres - Wang, Siyuan; Feng, Xiaobo; Liu, Ping; Wei, Youxiu; Xiao, Baojun (Current Pharmaceutical Biotechnology, 2020)
Background: PCL has a long history as an industrialized biomaterial for preparing microspheres, but its hydrophobic property and slow degradation rate often cause drug degeneration, quite slow drug release rate and undesirable tri-phasic release profile. Materials and Methods: In this study, we used the blending material of PLGA-PEG-PLGA and PCL to prepare microspheres. The microspheres degradation and drug release behaviors were evaluated through their molecular weight reduction rate, mass loss rate, morphology erosion and drug release profile. The hydrophilic PLGA-PEG-PLGA is expected to improve the degradation and drug release behaviors of PCL microspheres. Results: Microspheres in blending materials exhibited faster erosion rates than pure PCL microspheres, forming holes much quickly on the particle’s surface for the drug to diffuse out. A higher proportion of PLGA-PEG-PLGA caused faster degradation and erosion rates. The blending microspheres showed much faster drug release rates than pure PCL microspheres. Conclusion: With blending of 25wt% PLGA-PEG-PLGA, the release rate of microspheres speeded up significantly, while, with a further increase of PLGA-PEG-PLGA proportion (50%, 75%, 100%), it accelerated a little. The microspheres with PCL/PLGA-PEG-PLGA of 1/1 exhibited a linear-like drug release profile. The results could be a guideline for preparing microspheres based on blending materials to obtain a desirable release.
Keywords: degradation